Post-Colonial Ecocritical Dynamics in Ghosh's The Hungry Tide - Panta, Pradip (Dhaulagiri Journal of Contemporary Issues, 2024)
The dynamics of ecological systems of the bioregion i.e., the Sundarbans of the Bay of Bengal dominates the novel 'The Hungry Tide' by Amitav Ghosh. Here, I analyze how the text destabilizes and subverts the Universalist claim of Western superiority based on false dichotomy between nature and culture by applying postcolonial eco-critical insights. The basic tenet of postcolonial ecocriticism is that social injustice is embedded in the injustice of nature and it sees equity in both by rejecting Universalist claims of Eurocentrism which sees nature and local communities as resources. To prove the claim, the researcher has gone through theoretical critical insight of Graham Huggan and Helen Tiffin who talk about postcolonial ecocriticism. Besides, the researcher also used the eco-critical insight as per the need of the paper. The qualitative interpretative research is based on the textual analysis of the primary text applying the postcolonial eco-critical insights. The paper concludes that social inequality and injustice in nature must be eradicated so as to liberate both.